CompVision: An open-source five-compartmental software for biokinetic simulations - Beni Mehrdad Shahmohammadi (De Gruyter, 2021)
Simulations and numerical analysis of physical problems are important steps toward understanding underlying mechanisms of the processes. Important examples would be medical physics and medical imaging. Compartmental modeling has been found useful for estimating the transport and temporal variations of drugs/contaminants (commonly used in medical physics and medical imaging) in different organs, given that different organs would be modeled as compartments. Recycling among these modeled compartments (i.e., organs) was allowed through defining sets of constant transfer rates. In order to mathematically define these systems, one needs to use sets of differential equations (depending on the number of compartments) which would in fact be time-consuming and prone to mathematical error. Considering these issues, there is a need for a versatile computer program that is accurate, robust, and user-friendly to perform the required computations automatically. In the present work, we developed and benchmarked an open-source computer program entitled CompVision that was able to simulate five-compartmental systems. The present software had an easy-to-use graphical user interface (GUI) for the users. The executable program and the source codes were made available publicly under GPLv3 license, which would allow everyone to use, modify, and distribute without any restriction. The present program would be useful in a variety of research fields and applications.